Um modelo de simulação e operação de um sistema de irrigação com reservatórios em rios intermitentes - Carmo Filho, Arthur Arcanjo do (1978)
Selection of alternative for better use of the regulated water supply of on irrigation system for irrigation purpose was the objective of this study. Mathematical models for generation of monthly streamflow, for simulation of irrigation system and for reservoir operation were used. A methodology for the analysis of the structure of monthly streamflow series in intermittent rivers was used to identify a model for generation of monthly series. The critical period and the corresponding volume for a given regulated discharge were estimated for the set of generated series. Their frequency analysis was performed in order to analyze the reliability of supply. The irrigation water requirements for a set of selected crops were calculated and a simulation of the operation of the irrigation system was made using the criteria of maximum benefit and incremental areas. With the demands identified, the simulation of the operation of an equivalent reservoir system was performed. The application of the above methodology was made to the Morada Nova Project in the Banabuiu Valley in the State of Ceará.